GAMBARAN KEPEMILIKAN JAMBAN DI DESA PESODONGAN KECAMATAN KALIWIRO KABUPATEN WONOSOBO TAHUN 2020 - Dwi Atin Faidah (Jurnal Ilmiah Medsains, 2020)
One of the goals of the 17 Sustainable Development Goals (SDGs) at the sixth point is to ensure the availability of clean water and sustainable sanitation for everyone. Universal access to adequate sanitation are basic needs and human rights (WHO, 2017). The results of Basic Health Research (Riskesdas) in 2018 showed that the number of households in Indonesia using latrines is 88,2%. One of the districts in Central Java whose coverage of access to healthy latrines is still lowest is Wonosobo district (58%). 1n 2019, based on data from Kaliwiro Public Health Center, the coverage of healthy latrine access in Pesodongan village is still at 91%. The purpose of this study was to find out the description of ownership of latrines in Pesodongan Village, Kaliwiro Sub-District. This research is a descriptive study with a cross sectional research design approach. The study was conducted in April-May 2020. The sample in this study was 596 families. Data collection is done through secunder data from Kaliwiro Public Health Center. The data is processed through the process of cleaning, editing, coding, tabulating and entry and then performed statistical analysis using SPSS version 19.0. The statistical design used is univariate analysis. The results showed that the most respondents have permanent healthy latrines in Pesodongan Hamlet (52,7%), the most respondents have semi-permanent healthy latrines in Gintung Hamlet (62,5%), the most respondents who share latrines in Pesodongan Hamlet (42,9%) and most respondents who still have open defecation behavior in Majaina Hamlet (49,1%). It is hoped that the government will expected to be able to do more intensive triggering and provide assistance in the form of latrines that meet the requirements for residents who do not have latrines. Kata kunci : Jamban, Air Bersih, Kepemilikan Jamban, Sanitasi ABSTRAK Salah satu tujuan dari 17 point SDG’s pada point keenam adalah menjamin ketersediaan air bersih dan sanitasi yang berkelanjutan untuk semua orang. Akses universal ke sanitasi yang memadai adalah kebutuhan mendasar dan hak asasi manusia (WHO, 2017). Proporsi perilaku buang air besar di jamban untuk masyarakat Indonesia berdasarkan Riset Kesehatan Dasar tahun 2018 rata-rata nasional baru mencapai 88,2%. Kabupaten/ kota dengan persentase akses sanitasi layak terendah di Jawa Tengah adalah Wonosobo (58%). Berdasarkan data Puskesmas Kaliwiro capaian penduduk dengan akses sanitasi layak (jamban sehat) pada tahun 2019 Desa Pesodongan baru mencapai 91%. Tujuan dari penelitian ini adalah untuk mengetahui gambaran kepemilikan jamban di Desa Pesodongan Kecamatan Kaliwiro. Penelitian ini merupakan penelitian deskriptif dengan pendekatan desain penelitian yang digunakan adalah cross sectional. Penelitian dilaksanakan pada bulan April-Mei 2020. Sampel dalam penelitian ini adalah 596 KK. Cara pengumpulan data dilakukan melalui penggunaan data sekunder dari Puskesmas Kaliwiro. Data diolah dengan analisis univariat. Hasil penelitian menunjukan bahwa responden yang paling banyak mempunyai jamban sehat permanen (JSP) berada di Dusun Pesodongan (52,7%), responden yang paling banyak mempunyai jamban sehat semi permanen (JSSP) berada di Dusun Gintung (62,5%), responden yang paling banyak sharing/ numpang berada di Dusun Pesodongan (42,9%) dan responden yang masih mempunyai perilaku BABS paling banyak berada di Dusun Majaina (49,1%). Diharapkan kepada pemerintah bisa melakukan pemicuan lebih intensif serta memberikan bantuan pembuatan jamban.